Answer:
(D) multiply the second equation by -3 so that the x's have the opposite coefficients to then add the two equations together
Step-by-step explanation:
The given system of equations are:
[tex]3x+6y=12[/tex] (1)
and [tex]x+5y=10[/tex] (2)
Upon solving the given system of equations, multiply the second equation by -3 so that the x's have the opposite coefficients to then add the two equations together such that
[tex]3x+6y=12[/tex]
[tex]-3x-15y=-30[/tex]
Adding the above equations, we get
[tex]-9y=-18[/tex]
⇒[tex]y=2[/tex]
Substituting the value of y=2 in equation (1), we have
⇒[tex]3x+6(2)=12[/tex]
⇒[tex]3x+12=12[/tex]
⇒[tex]3x=0[/tex]
⇒[tex]x=0[/tex]
Hence, option D is correct.